Tantangan dan Strategi Penerapan Lingkungan Bahasa Arab di Pesantren - Muhammad Samin, Saproni; Akzam, Ismail; Pebrian, Rojja; Fikriansyah, Mahmud Harits (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
This study seeks to develop a strategy for the implementation of a conducive Arabic language environment in Islamic boarding schools. This study employs a qualitative research method with a descriptive research design. The target population consists of Islamic boarding schools in Riau that offer an Arabic language teaching program. The research sample comprises 12 Islamic boarding schools selected purposively based on the criteria of having an Arabic language teaching program and having participated in the community service program "Strengthening the Strategy for Implementing the Arabic Language Environment in Riau Islamic Boarding Schools". The research instruments utilized are questionnaires and interviews. Data analysis is conducted using descriptive analysis and content analysis. The findings of the study indicate that several Islamic boarding schools have implemented an Arabic language environment but still encounter challenges in the consistency of Arabic language use, limited facilities, and the number of teachers. This study recommends several strategies to enhance the effectiveness of implementing an Arabic language environment in Islamic boarding schools, including improving the quality of teachers, developing more effective learning materials, increasing student engagement in Arabic language activities, and intensifying the use of technology in Arabic language learning.